Pharmacological Management of Headaches - Mitsikostas, Dimos D.; Paemeleire, Koen (Headache, 2016)
In this book, headache experts summarize all the currently available therapies for primary headaches and, most importantly, describe the 'tricks' that can ensure the success of headache pharmacotherapy. Prevention and acute treatment of migraine and cluster headache receive particular attention, and individual chapters are devoted to the treatment of primary headaches in special groups, i.e., children, pregnant women, and the elderly. Further chapters focus on selected secondary headache disorders and cranial neuralgias for which pharmacotherapy is available. The book is designed to meet the daily practice needs of general physicians, general neurologists, neurologists in training, and medical students. Headache remains a leading reason for people to seek medical consultation, and migraine and other primary headache disorders are classified by the WHO as among the most disabling medical conditions in the general population, often affecting individuals during their most productive years. Unfortunately, undertreatment and mismanagement are the fate of many headache patients, and this book provides a sound basis for optimizing treatment.